Maritime Environmental Crisis: Public Administration as Master in the Global Marine Pollution Storm - Aris Sarjito (International Journal of Educational and Life Sciences, 2023)
This qualitative research delves into the multifaceted dynamics of the Maritime Environmental Crisis, focusing on the pivotal role of public administration in navigating the global marine pollution storm. The study explores marine pollution sources, environmental effects, public administration's role in preventing crises, the need for adaptable policies, and the significance of marine pollution-specific public administration. This qualitative research study uses secondary data sources to analyze marine pollution, emphasizing the need for targeted interventions, global impacts, public administration's role in crisis management, and adaptive administrative structures. In conclusion, the research positions public administration as the master orchestrator in the face of the global marine pollution storm, emphasizing the importance of strategic interventions and collaborative efforts to ensure a sustainable and resilient future.